A review on potential of natural products in the management of COVID-19. Issue 27 (12th May 2021) - Chakravarti, Rudra; Singh, Rajveer; Ghosh, Arijit; Dey, Dhritiman; Sharma, Priyanka; Velayutham, Ravichandiran; Roy, Syamal; Ghosh, Dipanjan
Abstract : In this review promising targets for drug development against SARS-CoV-2 and anti-viral activities of some of the known natural products (including plant secondary metabolites) are discussed. Abstract : At the end of 2019, a life threatening viral infection (COVID-19) caused by a novel coronavirus, Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) was reported. This virus has spread worldwide in a short duration and forced the world to face unprecedented life and economic loss. To date, there are no known specific drugs to combat this virus and the process for new drug development is lengthy. Most promising candidates, which emerged as potential leads, were abandoned in the later phases of clinical trials. Repurposing of already approved drugs for other therapeutic applications can be done only after extensive testing for safety and efficacy. With no definite therapeutics in the horizon, natural products are in extensive use arbitrarily as anti-viral agents and immune boosters. For ages it has been known that most natural products possess potent anti-viral activity and it is no different for SARS-CoV-2. It has been shown that natural products display inhibitory effects on MERS-CoV and SARS-CoV infections. In silico studies have shown that various natural products have strong binding affinity for and inhibitory action on the non-structural proteins of the virus, namely PL PRO, M PRO, and RdRp, and structural proteins such as spike (S) protein. Since the virus utilizes the transmembrane ACE2 receptor of the host cell, it also proves to be a valid target for drug development. In this review promising targets for drug development against SARS-CoV-2 and anti-viral activities of some of the known natural products are discussed.